Prevalence of anxiety symptoms and associated factors at 2 months postpartum, results from a 2021 French national prospective cohort study - Alexandra Doncarli; Virginie Demiguel; Camille Le Ray; Catherine Deneux-Tharaux; Elodie Lebreton; Gisèle Apter; Julie Boudet-Berquier; Catherine Crenn-Hebert; Marie-Noëlle Vacheron; Nolwenn Regnault; Sarah Tebeka; Members of the ENP2021 Study Group (European Psychiatry)
Abstract Background Postpartum anxiety (PPA) symptoms have harmful effects on child development and mother–infant interactions. Accordingly, in-depth knowledge of associated risk factors is crucial for prevention policies. This study aimed to estimate PPA symptom prevalence at 2 months and to identify associated risk factors in a representative sample of all women who gave birth in France in 2021, and in two subgroups: women with no postpartum depression (PPD) symptoms, and those with no history of mental health care.